Hapalindoles from the Cyanobacterium Hapalosiphon sp. Inhibit T Cell Proliferation - Chilczuk, Tomasz; Steinborn, Carmen; Breinlinger, Steffen; Zimmermann-Klemd, Amy Marisa; Huber, Roman; Enke, Heike; Enke, Dan; Niedermeyer, Timo Horst Johannes; Gründemann, Carsten (Planta Medica, 2020)
Novel immunomodulating agents are currently sought after for the treatment of autoimmune diseases and cancers. In this context, a screening campaign of a collection of 575 cyanobacteria extracts for immunomodulatory effects has been conducted. The screening resulted in several active extracts. Here we report the results of subsequent studies on an extract from the cyanobacterium Hapalosiphon sp. CBT1235. We identified 5 hapalindoles as the compounds responsible for the observed immunomodulatory effect. These indole alkaloids are produced by several strains of the cyanobacterial family Hapalosiphonaceae. They are known for their anti-infective, cytotoxic, and other bioactivities. Modulation of the activity of human immune cells has not yet been described. The immunomodulatory activity of the hapalindoles was characterized in vitro using flow cytometry-based measurements of T cell proliferation after carboxyfluorescein diacetate succinimidyl ester staining, and apoptosis and necrosis induction after annexin V/propidium iodide staining. The most potent compound, hapalindole A, reduced T cell proliferation with an IC50 of 1.56 µM, while relevant levels of apoptosis were measurable only at 10-fold higher concentrations. Hapalindole A-formamide and hapalindole J-formamide, isolated for the first time from a natural source, had much lower activity than the nonformylated derivatives while, at the same time, being less selective for antiproliferative over apoptotic effects.
Keywords: cyanobacteria; Hapalosiphon; hapalindoles; immune modulation; lymphocytes